Timeless Graffiti - Calderon Alaez, Elena (BBDS - Black Book: Drawing and Sketching, 2023)
The concept of liminality* that Arnold Van Gennep develops in his book entitled "Rites of Passage" (1909), is perfect to describe a new practice that has recently arrived in the art world: the sale of Street Art/Graffiti as pieces of NFTs. In recent months, numerous online platforms have emerged with the aim of monetizing this type of urban artistic expression, selling it through the blockchain as "non-fungible tokens". Numerous platforms boast of this sale, without considering the origins or bases on which this type of practice is based. The sale of only an animated mural painting (carried out legally and curated) in this case loses all meaning. The entire ethos of the “street” is lost. In our platform: TOTEMO.art the concept of liminality is perfectly captured. Our projects consist of the three phases of tripartite space-time (since we consider graffiti as a ritual technique, far removed from fine arts such as painting/sculpture/graphic design made in a studio). Our projects are therefore made up of a previous preliminary phase (carrying out the graffiti in the urban space and capturing videographic and photographic documentation of the process and the final piece), a liminal or intermediate phase (event with live art/live performance, where clients and visitors can experience and enjoy the creation process in person, both indoors and outdoors), and postliminal or later phase (animation and conversion into NFT and introduction to the blockchain: “minting process”, both from the final piece and from the creation). This "event" would be the place/moment (space/time) where trivial distinctiveness is suspended, which precisely allows "the passage", which Arnold Van Gennep speaks of, in his book, between one social condition and another: that is, between the underground/ urban to the highest spheres of collectors of blockchain pieces, between the physical and the virtual, between the ephemeral and the eternal, between the public and the private. Therefore, considering the origins of this almost “ritual” practice of graffiti, what would be the main weaknesses and opportunities of this emerging technology selling and collecting Street Art NFTs? What is the position of the artists facing this new form of monetization of their work? What meaning can we give it as art researchers and professionals? It seems that the advantage of these platforms is to convert these expressions (ephemeral that disappear due to vandalism, weather conditions, or due to the destruction of the support itself in the natural evolution of the city), into ETERNAL and IMMORTAL pieces within the blockchain. “Buildings can crumble, weather can cause damage, and developments can impede views,” explains artist Rachel Wolfe-Goldsmith, aka Wolfe Pack, who leaded an NFT Street art project the project. “By scanning a mural and turning it into an NFT, we forever immortalize the art”. But isn't this another of the reasons that characterize urban art and that in some way romanticize it? The artists choose the urban support knowing its conditions, and therefore play with the temporality of their pieces. They know that they will disappear in a short period of time, so do these artists agree that their pieces are IMMORTAL AND ETERNAL? Perhaps not all graffiti writers or street artists fully agree that the right thing to do is to turn these works into MONETIZABLE, COLLECTIBLE, TRADABLE, ENJOYABLE and ETERNAL pieces, as other platforms describe. While other artists find in the blockchain a new way to live from their art and to expand their creativity and recognition in the art world. In addition, the main factor that we always consider is the intellectual property of the piece. These works are made in the urban space, therefore, who can sell them? Is it lawful to appropriate them without taking into account the approval of the artist and sell them on our behalf? The first base from which we start and the most important for our platform is always to have the approval or even the collaboration of the artist himself. We can create NFTs that are going to be made in collaboration from scratch with the artist himself or sell pieces that are already part of the urban environment, but always with his approval. From the point of view of a conservator/restorer, this new initiative is fantastic since the pieces will be documented to a greater extent and gain more validation as an artistic category within the market and art history. Once again, we come into conflict with what is considered "urban art", because most of the platforms that sell this type of NFTs focus exclusively on selling what is classified as decorative "murals", but in none of the cases, other forms of urban expression have been included such as "tags", "graffiti" or "artistic interventions" such as "adbusting" etc... The form of documentation will therefore be more precise and, without a doubt, of higher quality, since the formats that are necessary for the creation of NFTs or animations must have a minimum resolution and the tools used for their documentation (either photo, video, 3D scan) are evolving to improve their quality. More emphasis will be also placed on the compilation of the type of techniques used and materials, geolocation…., of the pieces. The first platforms that are exclusively dedicated to this kind of NFTs, claim that “Street art” is the only form of art that “has never been monetized, commercialized, collected and enjoyed privately”. In part this is true (although there are very specific cases of globally famous artists in which even the pieces have been "torn" from their environment and are part of private collections. Also because their format allowed the translation, being small stencils, or tags, not of course huge murals). But maybe that’s exactly the main point. Perhaps "it has never been monetized, commercialized, collected and enjoyed privately" because its appearance arose from a totally opposite movement. In which it is sought that this type of art must be public, of free access, so that it can be enjoyed by everyone, even if they do not have economic resources or sufficient artistic knowledge. The important thing about our NFTs would be to live "experiences" (like this “smartbox” where you can buy and give away experiences) We do not sell a photo/video (or animated photo/video) of a final product. The important thing about these pieces has been the moment of its creation, the creation process, its elaboration. For this reason, events are a fundamental piece of our project, in which you can appreciate first-hand the creation and artistic process and the creation of live pieces, hand in hand with the artist. One of the fundamental parts of "urban art" is that it started completely illegally in the streets, and this is the factor that makes it unique. Selling a photo of the final result of a mural that has been made legally, does not have, from our point of view, greater interest than documenting the piece and for collectors, collecting these pieces as a chrome for an album. We want to sell with that final element, the creation process, of the artist, to know what materials, techniques he has used, the reason for that support, that location, the monitoring of security cameras, the police, access to the place, if he has acted alone, in company, etc... these processes and ways of acting are what truly make us understand this type of art and urban expression, and what make it unique. Perhaps the idea of ??selling a piece of street art/graffiti, in this way, is comparable to selling a skateboard. We have the final piece, but we lose the experience. In the case of skateboarding, the important thing is the execution, the act of skating. In the case of graffiti, it is the same. The important thing is the act of painting in a prohibited place, or in a difficult location. The final piece loses importance. And what really matters is the location and quantity (repetition of tags) in a place. Our mission or objective to stand out from other platforms that sell this type of art will be to focus on the movement and process of creating these pieces and not on the final result (as occurs in most large murals made legally and curated) , this does not mean that these works should not be the object of conservation and documentation as well, but we should now know how to differentiate between the sale as NFT of mural pieces (legal) and pieces of graffiti writers made illegally such as (tags, throwups, stickers , public interventions, carried out illegally). And those that therefore contain greater importance for us in the context of urban, secret, underground culture, movement, which must also be documented as part of the history of both art and even more socially, one could say of a certain place and community. Another advantage is that an NFT is a piece that can also include sound. The sound in this environmental case, or even of the object of execution or tool such as sprays, is also a fundamental aspect in the practice of graffiti. This act of painting (writing in the street) is almost imperceptible by most of the society, since most of these activities are carried out at night or in areas of difficult access or in a hidden way since most of them are about illegal activities. In Japan, as I already talked about in my previous article, the fines are very exaggerated, and it is even penalized with jail. Factor that makes these activities being carried out with greater care and dissimulation. Another advantage for this type of artist is to reach a much larger audience, and also to a field or environment that their pieces would never have reached were it not for the use of NFTs. We mean the world of the so-called “crypto bros”, and people focused on the field of crypto currencies but who are not familiar with the art world, and especially the street art/graffiti world. The use of secondary sales also opens a new world, thanks to those artists who are able to continue making an economic profit in the future, same as singers continue to get profit from their copyright. This allows some of these graffiti writers to make a living from it in the future, and we, as companies, will be more than grateful for the trust placed in us and for helping them make a living doing what they love. Both for us and for the artists, of course, it is one more way to monetize their art, but from our point of view also for art lovers and students, it is an unparalleled way of documenting this type of expression until now. Illegal and underground art and that it endures in the general culture on the blockchain just as the history of art has endured so far in textbooks. Perhaps in a few years NFTs will be studied as a new artistic movement. Or maybe it would be considered just a temporary trend. But at least already there you will find not only the final pieces, but also their execution process! Something fundamental in this type of artistic expression, considered as part as a whole street ritual. * Liminality is the quality of ambiguity or disorientation that occurs in the middle stage of a rite of passage, when participants no longer hold their pre-ritual status but have not yet begun the transition to the status they will hold when the rite is complete.